Long-Lived 1 H Singlet Spin States Originating from Para-Hydrogen in Cs-Symmetric Molecules Stored for Minutes in High Magnetic Fields - Franzoni, Maria Belen (2012)
Nuclear magnetic resonance (NMR) is a very powerful tool in physics, chemistry, and life sciences, although limited by low sensitivity. This problem can be overcome by hyperpolarization techniques dramatically enhancing the NMR signal. However, this approach is restricted to relatively short time scales depending on the nuclear spin-lattice relaxation time T1 in the range of seconds. This makes long-lived singlet states very useful as a way to extend the hyperpolarization lifetimes. Para-hydrogen induced polarization (PHIP) is particularly suitable, because para-H2 possesses singlet symmetry. Most PHIP experiments, however, are performed on asymmetric molecules, and the initial singlet state is directly converted to a NMR observable triplet state decaying with T1, in the order of seconds. We demonstrate that in symmetric molecules, a long-lived singlet state created by PHIP can be stored for several minutes on protons in high magnetic fields. Subsequently, it is converted into observable high nonthermal magnetization by controlled singlet-triplet conversion via level anticrossing.